Beauty Cosmetic Science, Cultural Issues and Creative Developments - Peaslee Levine, Martha; Scherer Santos, Júlia (IntechOpen, 2021)
Beauty - Cosmetic Science, Cultural Issues, and Creative Developments allows the reader to contemplate the many aspects of beauty. Within the book, there is a weaving together of external and internal beauty. Certainly, both influence each other. Some chapters focus on products that are used to care for oneself or work to enhance beauty. Other chapters look at media both commercial and social and the effects of those messages on one's acceptance of beauty. There are chapters that take us into the wilderness to explore our souls and teach us how we can spark our own creativity. This volume soars to encompass the limitless nature of beauty and plunges deep into internal connections to help us understand how we experience our own beauty.